2011
DOI: 10.4257/oeco.2011.1502.13
|View full text |Cite
|
Sign up to set email alerts
|

Revisão Dos Efeitos Do Fogo Sobre a Fauna De Formações Savânicas Do Brasil

Abstract: Entender como a biota responde aos eventos de fogo é de extrema relevância para o manejo e a conservação dos ecossistemas terrestres, especialmente em face das mudanças ambientais globais e do aumento das atividades antrópicas. Apresentamos aqui uma revisão dos artigos publicados até o ano de 2009 a respeito do efeito do fogo sobre a fauna das formações savânicas brasileiras. Dentre os 1.512 artigos encontrados na Web of Knowledge utilizando as palavras-chave "cerrado fire*" ou "savanna fire*", apenas 12 trata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 45 publications
3
48
1
24
Order By: Relevance
“…melanoticus, another species typical of the Brazilian savanna, did not change in abundance after the fire. Therefore, the fire can interfere with the survival rate of certain species, destroying their basic niche requirements, but can confer advantage to other species better adapted to live in more xeric conditions (Frizzo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…melanoticus, another species typical of the Brazilian savanna, did not change in abundance after the fire. Therefore, the fire can interfere with the survival rate of certain species, destroying their basic niche requirements, but can confer advantage to other species better adapted to live in more xeric conditions (Frizzo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most important biodiversity hotspots in the world due to species richness and a high percentage of endemism, containing more than 10,000 cataloged plant species [30,31], in which species display morphological and functional dependence from fire [32][33][34]. Several authors have shown that although fire-dependent ecosystems, such as the Cerrado, have evolved in the presence of recurrent natural fires and are dependent on them to maintain their biodiversity, high human pressure through frequent burning may have negative impacts on species diversity [35,36]. Fire is commonly used in agricultural land management, affecting water flow and facilitating erosive processes [37], and promoting deterioration of physical and chemical soil characteristics, reducing its productive potential [38].…”
Section: Study Area and Datamentioning
confidence: 99%
“…Another important factor driving anthropic fire occurrence is the introduction of exotic grasses that may cause a fast accumulation of inflammable biomass, enhancing fire occurrence (Cianciaruso, Silva, & Batalha, 2009). Changes caused by anthropic fires can affect animals in many ways, driven not only by the species sensitivity to the impact, but also by the fire intensity, frequency, and extension, allied to the proximity to unburned areas (Frizzo, Bonizário, Borges, & Vasconcelos, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor driving anthropic fire occurrence is the introduction of exotic grasses that may cause a fast accumulation of inflammable biomass, enhancing fire occurrence (Cianciaruso, Silva, & Batalha, 2009). Changes caused by anthropic fires can affect animals in many ways, driven not only by the species sensitivity to the impact, but also by the fire intensity, frequency, and extension, allied to the proximity to unburned areas (Frizzo, Bonizário, Borges, & Vasconcelos, 2011).Mainly in Savanna areas, an increase in fire frequency may affect several animal taxa such as arthropods (Swengel, 2001;Vasconcelos et al, 2009) To monitor the changes caused by fires, bioindicators have been used as a diagnostic tool to assess the impacts of human activities (Niemi & McDonald, 2004). Among the groups used for bioindication, insects offer faster responses, supporting an early diagnosis of the environment (Schowalter, 2006 (Silveira et al, 2013), and dominance (Andersen, 1991;Parr & Andersen, 2008).…”
mentioning
confidence: 99%